APLIKASI PROGRAM BELAJAR BERHITUNG UNTUK ANAK USIA 4-6 TAHUN DENGAN MENGGUNAKAN MACROMEDIA FLASH MX - Windayani Windayani; Marzuki, SKom, MMSI Marzuki, SKom, MMSI (Jurnal Sistem Informasi, 2005)
Scientific writing is about Application Numeracy Learning Programme For ChildrenAged 4-6 Years. This application contains math problems with drawings and colordisplay that must be adjusted to be calculated. This application also has an interactivedisplay interface. The program used was Macromedia Flash MX.This application is expected to assist children in learning to count to increaseintelligence and memory test children.